If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65 + -6X = 12X + 19 Reorder the terms: 65 + -6X = 19 + 12X Solving 65 + -6X = 19 + 12X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-12X' to each side of the equation. 65 + -6X + -12X = 19 + 12X + -12X Combine like terms: -6X + -12X = -18X 65 + -18X = 19 + 12X + -12X Combine like terms: 12X + -12X = 0 65 + -18X = 19 + 0 65 + -18X = 19 Add '-65' to each side of the equation. 65 + -65 + -18X = 19 + -65 Combine like terms: 65 + -65 = 0 0 + -18X = 19 + -65 -18X = 19 + -65 Combine like terms: 19 + -65 = -46 -18X = -46 Divide each side by '-18'. X = 2.555555556 Simplifying X = 2.555555556
| 9u^2-36v^2= | | 4+2a+6a=12 | | 4*x=60 | | 2n+5n=-21 | | 75x^3-12x=0 | | 49y^2-28y+4= | | v+1+4=10 | | m^3+6m^2-4m=0 | | a^2+8a-15=0 | | 116-4x=23x+17 | | ln(13)+ln(x)=0 | | 7b+1-b=1 | | x+7=-2(4x+10) | | 7-9x=46-30x | | 184-4x=41x+19 | | 6+x=-13 | | -42+y+2=44 | | y^2+6y-7=17 | | -x^2+6x-5=y | | -2n-n=-12 | | -7+6=x | | 9-10x=89-24x | | 5t-3t+8+4t-2=42 | | x-4+3x=12 | | x^2-2-20=0 | | r-4+6r=-4 | | 64s^2-4t^2= | | -3(2x-1)=x+10 | | -16x=-8+24x^2 | | 3x+9=-111-9x | | -2x=36 | | 5x=2y+4 |